2015
DOI: 10.1136/oemed-2015-102879
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hepatitis C among healthcare workers: a systematic review and meta-analysis

Abstract: The aim of this study was to estimate the prevalence of viral hepatitis C (HCV) infection among healthcare workers (HCWs) compared to the general population. A systematic search for the years 1989–2014 was conducted in the Medline, Embase and Cochrane databases. Studies on hepatitis C in HCWs were included if they incorporated either a control group or reference data for the general population. The study quality was classified as high, moderate or low. Pooled effect estimates were calculated to determine the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
2
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 71 publications
4
69
2
10
Order By: Relevance
“…In addition, a recent systematic review of international publications reported that health care workers in direct contact with patients or blood (from needle stick injuries) are 1.6 times more likely to be infected with HCV than the general population. Increased prevalence of HCV was found among medical staff (OR 2.2), laboratory staff (OR 2.2) and dental staff (OR 3.5) compared to controls (27). HCV outbreaks have also occurred in colonoscopy clinics in Canada (31-35).…”
Section: Contaminated Medical Dental or Personal Services Equipmentmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, a recent systematic review of international publications reported that health care workers in direct contact with patients or blood (from needle stick injuries) are 1.6 times more likely to be infected with HCV than the general population. Increased prevalence of HCV was found among medical staff (OR 2.2), laboratory staff (OR 2.2) and dental staff (OR 3.5) compared to controls (27). HCV outbreaks have also occurred in colonoscopy clinics in Canada (31-35).…”
Section: Contaminated Medical Dental or Personal Services Equipmentmentioning
confidence: 98%
“…in hospitals, dental offices) or personal service (e.g. tattoo parlours and nail salons) is another risk for HCV infection (26)(27)(28)(29)(30). For instance, patients undergoing hemodialysis are at increased risk of acquiring HCV, especially if the equipment has been reused or improperly sterilized (26).…”
Section: Contaminated Medical Dental or Personal Services Equipmentmentioning
confidence: 99%
“…In a recent meta-analysis, the reported AHC estimates among health care workers (HCW) from 1989 to 2014 had exceeded 200% higher prevalence than the public [10]. Furthermost, the situation is more critical in developing countries e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermost, the situation is more critical in developing countries e.g. Egypt, and Nigeria, which are cursed by the triad of poverty, illiteracy, and of course disease [10]. Needle stick injuries are verified as the most deleterious risk accidents among HCW with an average rate of HCV infection of 0.5% [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation